PENGARUH FAKTOR MAKROEKONOMI DAN KEBIJAKAN MONETER NEGARA MAJU TERHADAP YIELD OBLIGASI INDONESIA - Fajar Akbari; Sri Ulfa Sentosa (Universitas Negeri Padang, 2019)
This study aims to determine the influence of macroeconomic factors and monetary policy of developed countries on Indonesian bond yields. The independent variables in this study are inflation as X1, foreign exchange reserves as X2, M2 money supply as X3, American interest rates as X4, European interest rates as X5, and the dependent variable of Indonesian government bond yield as Y. The data used is secondary data in the form of time series data from 2008Q1 to 2018Q4, with data collection techniques, namely documentation from Bank Indonesia publications, Central Statistics Agency, investing.com sites and library studies. The research method used is (1) Multiple Linear Regression, (2) Classical Assumption Test, (3) coefficient of determination. The results of this study indicate that: (1) inflation has a significant positive effect on Indonesian bond yields. (2) Foreign exchange reserves have a significant negative effect on Indonesian bond yields. (3) M2 money supply has no effect on Indonesian bond yields. (4) American interest rates have a significant positive effect on Indonesian bond yields. (5) European interest rates do not have a significant positive effect on Indonesian bond yields.